Factors Influencing Capitation Fund Utilization in Public Health Centers - Solehudin Al Ayubi; Adya Hermawati; Eka Wilda Faida (International Journal of Multidisciplinary Sciences and Arts, 2026)
This study examines the effects of the National Health Insurance (Jaminan Kesehatan Nasional/JKN) program socialization, service accessibility, service quality, and health workforce competence on the utilization of capitation funds at the Mayamuk Public Health Center, Sorong Regency, Indonesia. It also investigates whether health center characteristics, community characteristics, and internal policies moderate these relationships. A quantitative approach was applied using a survey method. The study population comprised JKN outpatient participants within the service coverage area of the Mayamuk Public Health Center. Samples were selected through probability sampling based on predefined inclusion criteria. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the support of SmartPLS software. The findings reveal that JKN program socialization, service quality, and health workforce competence have a positive and statistically significant effect on the utilization of capitation funds. In contrast, service accessibility does not demonstrate a significant effect. Simultaneously, the independent variables collectively exert a significant influence on capitation fund utilization. However, health center characteristics, community characteristics, and internal policies are not found to moderate the relationships between the independent variables and capitation fund utilization. These results indicate that the effectiveness of capitation fund utilization in public health centers is primarily determined by institutional and human resource factors rather than by accessibility or contextual moderating factors. Therefore, policy interventions should prioritize strengthening JKN program socialization, enhancing service quality, and improving health workforce competence to optimize capitation fund management, particularly in resource-constrained regions such as Sorong Regency.